Visualization of label-free titanium dioxide nanoparticle deposition on surfaces with nanoscale roughness. Issue 1 (6th December 2018) - Kananizadeh, Negin; Peev, Darin; Delon, Thompson; Schubert, Eva; Bartelt-Hunt, Shannon; Schubert, Mathias; Zhang, Jianming; Uhlmann, Petra; Lederer, Albena; Li, Yusong
Abstract : An innovative technique to quantify and visualize label-free titanium dioxide nanoparticles on model rough surfaces. Abstract : Understanding the transport of engineered nanoparticles (ENPs) and their interaction with environmental surfaces is critical to predicting their fate and environmental implications. Here, we report an innovative technique to visualize and quantify the deposition of titanium dioxide nanoparticles (TiO2 NP) on engineered surfaces with nanoscale roughness, i.e., slanted columnar thin films (SCTFs). The attachment of TiO2 NP on the surface of SCTFs changed the optical property of SCTFs, which was detected using a generalized ellipsometry (GE)-based instrument, an anisotropy contrast optical microscope (ACOM). An anisotropic effective medium model was applied to quantitatively analyze ACOM images of SCTF surfaces, which provided the mass distribution of TiO2 NP. The TiO2 NP mass measured by ACOM was in good agreement with the known amount of TiO2 NP mass dispersed by controlled piezoelectric plotting. The detection of a few picograms of nanoparticle mass by an individual pixel measuring 7 × 7-micrometer squared was demonstrated. Further, a glass microfluidic channel with SCTF embedded was developed. The areal mass density of attached TiO2 NP on SCTF surfaces as they flow through the channel under various flow rates was quantitatively measured in situ . At the end of the experiment, the distribution of the attached TiO2 NP on the SCTF surface was visualized. The averaged mass density estimated by integrating the distribution map was in close agreement with the estimation from dynamic measurements and between repeating experiments. The capability of this novel technique to sense, quantify and visualize the mass distribution of TiO2 NP provides a valuable approach to investigate the behavior of nanoparticles at the interface of flow and rough surfaces.